Compatibility charts of BRB-VD combined systems for RC frames in ultra-high seismic intensity zones - Lan, Shuwei; Liu, Yu; Lan, Xiang; Wu, Kechuang (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
The combined seismic energy dissipation of BRB and VD in ultra-high seismic zones leverages their strengths, producing a hybrid damping system with excellent performance and significant application potential. Although the potential of such combined damping systems in seismic design is widely recognized, the lack of a clear methodology for coordinating their distinct stiffness and damping mechanisms remains a major barrier to their effective implementation. To solve the compatibility issue between the two technologies, we perform a series of computational analyses of reinforced concrete frame structures equipped with BRB-VD combined systems in ultra-high seismic zones. The analysis determines key parameters, including the nominal lateral stiffness ratio K of BRBs and the additional damping ratio ξa provided by VD. As a result, the K-ξa relationship charts illustrating the compatibility between the two dampers under different seismic design groups in ultra-high seismic zones are developed, eliminating the inconvenience caused by multiple iterations based on the response spectrum design method. The accuracy and practicability of the K-ξa relation charts for combined seismic energy dissipation design are further validated through engineering examples, providing a convenient manual calculation tool for structural engineers and offering valuable references for similar high-seismic regions aroundthe world.